Controlling the rotation of asymmetric top molecules by the combination of a long and a short laser pulse - Viftrup, Simon S.; Kumarappan, Vinod; Holmegaard, Lotte; Bisgaard, Christer Z.; Stapelfeldt, Henrik; Artamonov, Maxim; Hamilton, Edward; Seideman, Tamar (My University, 2009)
We describe theoretically and experimentally a laser-based method to control the rotations of asymmetric top molecules in three-dimensional space. Our method relies on keeping one axis of a molecule essentially fixed in space along the polarization vector of a nanosecond laser pulse (termed the long pulse) and forcing the molecule to rotate about the aligned axis by an orthogonally polarized, femtosecond laser pulse (termed the short pulse). Experimentally, we use femtosecond timed Coulomb explosion to image the three-dimensional (3D) alignment of the 3,5-difluoroiodobenzene molecule as a function of time after the short pulse. Strong 3D alignment is observed a few picoseconds after the short pulse and is repeated periodically, reflecting directly the revolution of the molecular plane about the aligned axis. Our numerical results, based on nonperturbative solution of the time-dependent Schrödinger equation, are in good agreement with the experimental findings and serve to unravel the underlying physical mechanism of the observations. The experiments and theory explore the influence of the laser parameters on the rotational control, in particular the role played by the intensity of the long and the short laser pulses. To illustrate the generality of our method, we illustrate its applicability to a molecule (3,4-dibromothiophene), with significantly different inertia and polarizability tensors. Finally, our theory shows that the strong 3D alignment obtained by the combined laser pulse method can be converted in to field-free alignment by rapid truncation of the long laser pulse.